PENGARUH PENGGUNAAN MULTIMEDIA CD INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 09 TANJUNG SAKTI PUMU - Livia Afrizah Pintasti; Dessy Wardiah; Aldora Pratama (STKIP Subang, 2023)
Background of this research that learning activities are less effective because in the teaching and learning process teachers tend to use tools in the form of simple media, so it is less interesting to be noticed by students. This study aims to determine the effect of using Interactive Multimedia CD on the learning outcomes of grade IV students of SD Negeri 09 Tanjung Sakti Pumu. This research was conducted at SD Negeri 09 Tanjung Sakti Pumu located in Gunung Raya Village, Tanjung Sakti Pumu District, Lahat District, South Sumatra, with zip code 31581. This research is a type of experimental research, namely the type of pre-Experimental Design. The population and sample in this study were grade IV students of SD Negeri 09 Tanjung Sakti Pumu, totaling 20 people. Data collection techniques in this study are Test, Observation and Documentation. Data analysis techniques in this study include Normality Test, Homogeneity Test, Hypothesis Test. The result of this study is a hypothesis test showing that t count ≥ t table or 11.251 ≥ 2.110, then it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of interactive multimedia CDs on the learning outcomes of grade IV students of SD Negeri 09 Tanjung Sakti Pumu.